2021
DOI: 10.1002/ppul.25610
|View full text |Cite
|
Sign up to set email alerts
|

Association of time of first corticosteroid treatment with bronchopulmonary dysplasia in preterm infants

Abstract: Objective To evaluate the association between the time of first systemic corticosteroid initiation and bronchopulmonary dysplasia (BPD) in preterm infants. Study design A multi‐center retrospective cohort study from January 2010 to December 2016 using the Children's Hospitals Neonatal Database and Pediatric Health Information System database was conducted. The study population included preterm infants <32 weeks' gestation treated with systemic corticosteroids after 7 days of age and before 34 weeks' postmenstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Indeed, betamethasone was used in 6.4% of the study population, and the mean time-point of the first administration was at 27.6 DOL. The first administration time of betamethasone in our study is consistent with recent findings on the association between timing of systemic PC and severity of BPD ( Harmon et al, 2020 ; Cuna et al, 2021 ). Results from two retrospective cohorts of very ( Cuna et al, 2021 ) and extremely ( Harmon et al, 2020 ) preterm infants, showed that later treatment (after DOL 36 and DOL 50 respectively) was associated with increased likelihood to develop severe BPD, compared to earlier treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, betamethasone was used in 6.4% of the study population, and the mean time-point of the first administration was at 27.6 DOL. The first administration time of betamethasone in our study is consistent with recent findings on the association between timing of systemic PC and severity of BPD ( Harmon et al, 2020 ; Cuna et al, 2021 ). Results from two retrospective cohorts of very ( Cuna et al, 2021 ) and extremely ( Harmon et al, 2020 ) preterm infants, showed that later treatment (after DOL 36 and DOL 50 respectively) was associated with increased likelihood to develop severe BPD, compared to earlier treatment.…”
Section: Discussionsupporting
confidence: 92%
“…234 Receipt of steroids >36 days of life was associated with approximately twice the risk for Grade 2 or 3 BPD when compared to exposure between 8 and 21 days of life [aOR: 2.0, 95% CI: 1.1-3.70] in a retrospective study conducted by centers enrolled in the Children's Hospital Neonatal Consortium (CHNC). 235 Although it seems surprising that almost half of the patients in this cohort received their first dose of systemic corticosteroids in the 8-21-day timeframe, a much higher proportion of infants in this group received hydrocortisone (77.9%) versus dexamethasone (22.1%) when compared with those that received later treatment. 235 Clinicians may be more willing to use hydrocortisone before 21 days of life as unlike dexamethasone, early postnatal hydrocortisone use has not been linked to neurodevelopmental impairment.…”
Section: Dovepressmentioning
confidence: 84%
“…235 Although it seems surprising that almost half of the patients in this cohort received their first dose of systemic corticosteroids in the 8-21-day timeframe, a much higher proportion of infants in this group received hydrocortisone (77.9%) versus dexamethasone (22.1%) when compared with those that received later treatment. 235 Clinicians may be more willing to use hydrocortisone before 21 days of life as unlike dexamethasone, early postnatal hydrocortisone use has not been linked to neurodevelopmental impairment. 107,236,237 No evidence of adverse outcomes has been noted in the follow-up of participants in the SToP BPD Trial, who received later, higher doses of hydrocortisone; 237 however, there is as yet no evidence from RCTs that treatment with hydrocortisone beyond the first week of life is helpful in reducing BPD even for higher risk populations.…”
Section: Dovepressmentioning
confidence: 84%
“…14 Later initiation of systemic hydrocortisone or dexamethasone treatment was associated with higher odds of Grade 2 or 3 severe BPD, and a positive correlation was observed between the initiation after 35 days of life and the rate of severe BPD at 36 weeks' postmenstrual age in a recent multicenter retrospective study of PNCS-treated preterm infants. 57 In addition, there are few data on the long-term neurodevelopmental effects of late hydrocortisone therapy.…”
Section: Systemic Pncssmentioning
confidence: 99%